PRESENTATION OF THE SECOND INTERNATIONAL SYMPOSIUM ON SCIENCE AND BIOTECHNOLOGY - Gelinski, Jane Lafayette Neves (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
PRESENTATION Dear Colleagues It was a great pleasure that we conducted the II International Symposium on Science and Biotechnology-II ISSB – Entrepreuneurship and Innovation with support of the Science and Biotechnology Graduate Program from Universidade do Oeste de Santa Catarina, in Videira, Brazil, between the 04th and 110th of november 2017. We led a very good scientific program that met the expectations of professionals and students. The event was planned to be a discussion forum and with the aim of expanding the professional partnerships on biotechnology and innovation. Now we present the Proceedings of II ISSB with abstracts of research in two Areas: Biotechnology Applied to Agroindustry and Health / Environmental Biotechnology. We hope that it can be a good source of scientific knowledge and information. We hope see all of you at III ISSB! SCIENTIFIC COMMITTEE II ISSB November 10, 2017 Videira, SC – Brazil